Performance Test Hammer Mill With Corn Feed Corncob - Octa Rahmadian; Sugeng Triyono; Warji Warji (The University of Lampung, 2012)
Corn cob is one abundant agricultural waste and potentially viable for animal feed. Objective of this research was to test a hammer mill to crush the corn cob. The study was made in two different rotational speeds, 800 rpm and 1400 rpm. A perforated screen (underneath the rotating hammer drum) with 1 cm hole size was used. The test was conducted in three replications and each replication used 5 kg corn cob. Variables observed included uniformity of grain sizes of the product and machine capacity. The expected grain sizes ranged 3 to 7 mm. The results showed that this machine performed better under 1400 rpm than under 800 rpm. With 1400 rpm, the machine produced the expected grain sizes of the product about 45,57% by weight, and had a capacity about 15,62 kg/hour. Keywords: Corn cob, Hammer mill, Capacity, Energi consumtion.